Dental Education in the Time of COVID-19 Pandemic: Challenges and Recommendations - Hassan, Mohamed G.; Amer, Hala (Frontiers in Medicine, 2021)
Moving within the second wave of the coronavirus (COVID-19) pandemic, dental education delivery has been profoundly affected by this crisis, so has the structure, evaluation, and future of dental education. Both pre-clinical and clinical dental education have experienced challenges ranging from fully online educational content to limited dental training for senior dental students. This crisis appears to be a tipping point that produced confusion in dental teaching especially clinical sciences. Although medical institutions immediately started to adapt to the unexpected COVID-19 crisis, dental and oral health educational services are profoundly impaired due to the dental team's propinquity to the patient and the aerosols generated during routine dental therapeutic procedures. Dental students unlike other medical students are considered to be at the highest risk due to the nature of their clinical training that includes working in the oral cavity of patients using aerosol-generating equipment. Some dental schools have taken the leadership and documented their modifications during this pandemic; however, there is a serious need for further investigation and wide range screening of the situation in the dental schools during the COVID-19 crisis. The aim of this mini-review is to present these challenges and how academic dental institutions have implemented strategies to overcome them.